Immunogenicity and safety of two quadrivalent influenza vaccines in healthy adult and elderly participants in India - A phase III, active-controlled, randomized clinical study. Issue 1 (31st January 2022) - Basu, Indraneel; Agarwal, Manish; Shah, Viral; Shukla, Vijay; Naik, Sunil; Supe, Pravin Dinkar; Srivastava, Manoj Kumar; Giriraja, Kanakapura Vrushabaiah; Pinjar, Peersab; Mishra, Pradeep Kumar; Joshi, Shishir; Vijayakumar, Ranjit; et al.
ABSTRACT: Background: This study was conducted to compare the immunogenicity and safety profile of two quadrivalent influenza vaccines (QIVs) in healthy adults (18–60 years) and elderly (>61 years) participants. Method: This phase III study was conducted from March 2018 to April 2018 across 12 sites in India. In this randomized, observer-blind, active-controlled study, 480 participants were randomized to receive a single dose of test vaccine (subunit, inactivated influenza vaccine; Influvac® Tetra, Abbott) (n = 240) or reference vaccine (split virion, inactivated influenza vaccine; VaxiFlu-4, Zydus Cadilla Healthcare) (n = 240). The primary objective was to describe and compare the immunogenicity of each vaccination group based on hemagglutination inhibition (HI) assay seroprotection and seroconversion rates, and geometric mean fold increase (GMFI) against four vaccine strains in two age groups. Safety and reactogenicity were also compared for the vaccines in both the age groups. Results: The pre- and post-vaccination HI titers for both the vaccines were comparable. The GMFI varied from 4.3 – 22.7 in the test and 3.7–21.6 in the reference vaccine group. The seroprotection rates were >90% for the A-strains and ranged between >43% and <60% for B-strains for both the vaccines. Seroconversion rates varied between 41.4% and 78.8%. Overall, the reported adverse events (AEs) for both the vaccines were <1% and comparable. Reported local and systemic reactions were comparable. Conclusion: Influvac® Tetra elicited an adequate immune response with a favorable safety profile which was comparable with the reference vaccine. (Clinical trial registry number: CTRI/2018/02/012222)